Dampak Kerusakan Lingkungan terhadap Bencana Alam (Studi Kasus di Rintisan Desa Wisata Wonosoco Kecamatan Undaan Kabupaten Kudus) - Elyawati, Elyawati; Fatmawati, Noor (IJTIMAIYA: Journal of Social Science and Teaching, 2021)
Forests are the largest natural wealth owned by Indonesia, which contains thousands of species of living things, both animals, plants and the human race. Forests must be protected and preserved by the caliphs of the earth for their survival. But the greedy attitude of humans makes forests in Indonesia arid because the environment does not have enough water absorption so that disasters occur everywhere and become a problem in Indonesia every year. The purpose of this research is to collect information based on data from the location and provide insights so that the public is aware of and understands the importance of preserving the beautiful natural environment in the Kendeng Mountains area which frequently occurs flash floods and landslides. This research method uses a literature study research method from two references, namely the primary reference, namely data collection which is carried out directly without intermediaries and secondary references obtained from documents, books, journals, etc. The results of this study indicate a relationship between environmental damage that occurs with human actions who lack awareness of environmental preservation. The Wonosoco people who live in the foothills of the Kendeng mountains still need socialization about the importance of preserving nature. The need that makes their excuse to cut trees so that the forest becomes deforested, but there must be an effort to replant it to reduce major risks.